(untitled) (Research, Society and Development, 2020)
Alternatives that enable the full use of food items are of great relevance in view of the high volume of wasted food, especially fruit. This way, the development of fruit residue flour arises as a possibility to reduce production losses, in addition to contributing with nutritional components that provide better quality of life. Given the above, the objective of this study was to demonstrate the feasibility of using flour from the residue of fruit produced in Brazil as ingredients in yoghurt production, presenting a review of studies that evaluated the effects that the inclusion of these flours had on the physicochemical, nutritional, functional, technological, and sensory characteristics of the products. Thus, the results presented by the research demonstrate that the use of Brazilian fruit residue flour as alternative ingredients in the production of yoghurts with functional properties is feasible, since some of the flour adds nutritional, functional, and economic value to the yogurt, without loss of sensory and technological quality in the final product.